Vietnam's integration into the Mekong subregion: an approach from the perspective of international institutions ("Journal "U". Economy. Management. Finance.", 2025)
The integration of Vietnam into the Mekong subregion is an important topic for research from the point of view of international institutions. It is of interest to study the place and role of Vietnam in the process of integration into the Mekong subregion, as well as to identify the mechanisms of interaction that affect the socio-economic development of the country. The article examines the specifics of the integration processes taking place in the Mekong subregion. The article presents the features of the Mekong subregion and the approach of international institutions to the process of Vietnam's integration into this subregion. The authors will analyze the process of Vietnam's integration into the Mekong subregion through the prism of several key international institutions from 2016 to the present. In conclusion, the conclusions and recommendations that can be used in the process of developing Vietnam's foreign policy on integration into the Mekong subregion are presented. The article will be of interest to researchers dealing with the problems of economic integration of Southeast Asian countries, in particular Vietnam.
Keywords: international institutions; integration; the Mekong subregion; Vietnam